การศึึึกษาคุณลักษณะของปุ๋ยหมักที่ได้จากกากตะกอนของระบบบำบัดน้ำเสียของวัสดุอินทรีย์ - ปรมีศนาภรณ์, ยุวรัตน์ (Journal of Food Health and Bioenvironmental Science, 2013)
Abstract This study aims to investigate the efficacy of Thai neem tree seed (Azadirachta indica var siamensis), Tagetes patula Linn. root and Eupatorium odoratum Linn. leaves and stems extracts with hexane dichloromethane methylalcohol and distillated water on control and eradication of the stage 2 Musca domestica maggots, which are non-chemical resistance breeding. The toxic results exhibited LC50 values at 48 and 72 hours. The result showed that Thai neem tree seed extract had the greatest effect in controlling the stage 2 Musca domestica maggots. The enriched neem extract, crude extract and dissolved distillated water extract were tested against the stage 2 Musca domestica maggots using feeding method, which occurred at 48 hrs. and LC50 (lethal dose) = 5.05, 4.80 and 20.12 milligram/litre respectively. LC50 (lethal dose) at 72 hrs. = 4.81, 4.63 and 19.12 milligram/litre respectively. The Tagetes patula Linn. root extracted with methyl alcohol at 95% concentration were carried out to control the stage 2 Musca domestica maggots at 48 and 72 hrs., LC50 (lethal dose) = 194.56 and 200.75 milligram/litre. The Eupatorium odoratum Linn. leaves and stems extracts at the concentration of 20, 40, 60, 80 and100 milligram/litre did not show any feeding poison against the stage 2 Musca domestica maggots, which developed into puparium stage. Keywords : Musca domestica maggots, Botanical insecticide, Azadirachta indica var. siamensia Val. seed, Tagetes patula Linn. root, Eupatorium odoratum Linn. leaves